Powerful Women in Anggy Umbara’s Web Series: Layangan Putus - Devi Crisilia Amabel Wiliana (Institute of Research and Community Outreach - Petra Christian University, 2023)
Layangan Putus is a web series adapted from a novel by Drh. Eka Nur Prasetya. In this article, I am analyzing this series because there is a hidden gem in these five female characters, which shows their power to fight for their rights and happiness. For that, I am interested in analyzing their power and what consequences they receive. In my analysis, I use the girl power theory based on the descriptions by Zaslow (2017), Inness (2004), and Bettis & Addams (2005) on girl power, which is independent, smart, and assertive. I analyze the way these five female characters exercise their power by being independent, smart, and assertive. As the consequences of exercising their power, they experience positive and negative results. For the positive result, they get what they want in life such as individual freedom, and for the negative one, they have to sacrifice important things such as their feelings, and personal relationships. In conclusion, in exercising their power, they gain self-growth and self-discovery.